Life-long prevention of cardiovascular disease. Part II: childhood and adolescence - O. V. Kopylova; A. I. Ershova; A. N. Meshkov; A. V. Kontsevaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
In recent years, researchers have increasingly noted that the development and health of cardiovascular system is influenced by both traditional risk factors (RF) and other determinants of human exposome — a combination of factors of the external and internal environment that affect genetics and epigenetics, as a result of which, one or another (more or less healthy) phenotype is formed. Exposome components have a continuous effect throughout all periods of life. Many RFs have a cumulative effect, and therefore it is important to start prevention of cardiovascular diseases (CVDs) as early as possible. The aim of this review was to consider various aspects of CVD prevention in childhood and adolescence. These periods are critical for the development of most behavioral habits, which maintain throughout life. Leading by personal example by parents and the immediate environment plays a paramount role in healthy lifestyle inclusion of children and adolescents. Targeted programs in kindergartens and schools aim at improving health literacy, early detection and timely changing traditional and non-traditional CVD RFs, diagnosis of genetic diseases involving the heart and blood vessels, prevention of sudden cardiac death are also important methods of CVD prevention in childhood and adolescence. Measures of population-based prevention are of great importance, including monitoring of advertising and media content, statutory ban of alcohol and tobacco sale, and the formation of healthy lifestyle.